Control of Cross Talk between Angiogenesis and Inflammation by Mesenchymal Stem Cells for the Treatment of Ocular Surface Diseases - Fei Li; Shao-zhen Zhao (Stem Cells International)
Angiogenesis is beneficial in the treatment of ischemic heart disease and peripheral artery disease. However, it facilitates inflammatory cell filtration and inflammation cascade that disrupt the immune and angiogenesis privilege of the avascular cornea, resulting in ocular surface diseases and even vision loss. Although great progress has been achieved, healing of severe ocular surface injury and immunosuppression of corneal transplantation are the most difficult and challenging step in the treatment of ocular surface disorders. Mesenchymal stem cells (MSCs), derived from various adult tissues, are able to differentiate into different cell types such as endothelial cells and fat cells. Although it is still under debate whether MSCs could give rise to functional corneal cells, recent results from different study groups showed that MSCs could improve corneal disease recovery through suppression of inflammation and modulation of immune cells. Thus, MSCs could become a promising tool for ocular surface disorders. In this review, we discussed how angiogenesis and inflammation are orchestrated in the pathogenesis of ocular surface disease. We overviewed and updated the knowledge of MSCs and then summarized the therapeutic potential of MSCs via control of angiogenesis, inflammation, and immune response in the treatment of ocular surface disease.